Political Science and U.S. Health Policy in the Era of the Affordable Care Act. (14th May 2020) - Haeder, Simon F.
Abstract : Few laws have a profound and lasting impact on an entire political system. The Affordable Care Act (ACA), despite its incremental nature and bipartisan heritage, has been one of those remarkable landmarks. Even a decade after its passage, the political struggle is far from over, as the ACA is still facing near constant threats from the incumbent president, Congress, the courts, statehouses, attorneys general, and governors across the nation. How have political scientists responded to the continued struggle? This article provides an overview of the effects of health reform and the ACA on political science research since 2008. While political scientists have written much about the subject, coverage has been distinctly uneven within the discipline. Indeed, it has almost been entirely confined to scholars of public and health policy. Nonetheless, there have been important contributions across disciplinary fields. This article provides an overview of contributions embedded within the study of federalism, policy feedback effects, and political framing. It concludes by emphasizing the need for more engaged scholarship on health policy issues from across the entire discipline, and by highlighting other areas of study that could benefit from broader attention by political scientists.